2018
DOI: 10.1007/s10072-018-3297-2
|View full text |Cite
|
Sign up to set email alerts
|

Benton visual form discrimination test in healthy children: normative data and qualitative analysis

Abstract: The attention evaluation may be considered a crucial phase in neuropsychological assessment. It must take into account the systemic nature of the attentional functions and must use different reliable tests in relation to the neurological and attentional problems to be addressed. The aim of the study was to offer the clinician an effective tool for attention assessment and provide the normative data and performance analysis on the Benton Visual Form Discrimination Test on an Italian sample (number 323) of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Six-year-old children proved able to identify the missing element to complete a continuous or discrete pattern, even in the presence of alternative choices as distractors, and from an early age, visuo-spatial attentive abilities implied in attentive problems of this cluster items appears sufficiently organised. These findings are consistent with a previous study [64] that showed that children from the age of nine and up performed almost as well as the adult control group in a complex visual discrimination tasks, such as Benton's Visual Form Discrimination Test [65].…”
Section: Discussionsupporting
confidence: 92%
“…Six-year-old children proved able to identify the missing element to complete a continuous or discrete pattern, even in the presence of alternative choices as distractors, and from an early age, visuo-spatial attentive abilities implied in attentive problems of this cluster items appears sufficiently organised. These findings are consistent with a previous study [64] that showed that children from the age of nine and up performed almost as well as the adult control group in a complex visual discrimination tasks, such as Benton's Visual Form Discrimination Test [65].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, OSAS may be associated with several comorbidities 2. Neurocognitive and cardiovascular complications, obesity, daytime sleepiness, hypertension, impaired growth, and learning and behavioral problems,36 as well as attention, executive functions, and memory difficulties have been documented in children with OSAS 710. Abnormal neuronal metabolites were detected in the hippocampus and frontal cortex of OSAS children 11.…”
Section: Introductionmentioning
confidence: 99%
“…Action VGs have even been used to treat dyslexic children [ 46 , 47 ]. Only 12 h of action VGs, for nine sessions of 80 min per day, significantly improved reading and attentional skills [ 48 ].…”
Section: Resultsmentioning
confidence: 99%